Palynology of the Kanguk formation (late cretaceous), Remus Creek, Ellesmere Island, Canadian Arctic Archipelago - Nunez-Betelu, Luis (Koldo) M. (University of Calgary, 1991)
Bibliography: p. 193-227. The stratigraphic nature, palynological constituents, and petroleum potential of the Kanguk Formation and contiguous strata have been assessed by combining palynology, sedimentology, and Rock-EvalffOC pyrolysis. In the northeastern Sverdrup Basin the Kanguk is latest Cenomanian/early Turonian to Campanian in age. It constitutes a depositional sequence bounded by two major unconformities throughout the study area except at Remus Creek. The lower unconformity spans the Albian-latest Cenomanian/Turonian interval whereas the upper unconformity includes the late Campanian-Paleocene interval. Both unconformities are diachronous. In the northeastern Sverdrup Basin the Kanguk Fonnation can be traced from coastal areas (Mount Bridgman) westward to offshore areas (Glacier Fiord). Marine and terrestrial palynomorphs are well-preserved and represented by 428 taxa, including 226 marine and 202 terrestrial species. One new marine dinocyst genus (lbaidinium g. nov.), seven new marine dinocyst species (Chatangiella kangukensis sp. nov., lbaidinium canadensis sp. nov., lbaidinium inuitei sp. nov., lbaidinium mertxei sp. nov., Luehndea brevispinosa sp. nov., Odontochitina octopusa sp. nov., and Trithyrodinium verrucosum sp. nov.) and a new terrestrial pollen species (Wodehouseia arctica sp. nov.) have been recognized. The genus Ibaidinium g. nov. and the species Odontochitina octopusa sp. nov. are age-significant and restricted to the latest Coniacian. Based on the palynological content, the Kanguk Formation can be subdivided into a lower marine dominated interval and an upper terrestrial dominated interval. The formation has been subdivided into four biozones. The upper three biozones roughly correlate with previously established biozones for the Kanguk Formation or equivalent units. A combination of sedimentological and Rock-EvalffOC pyrolysis data supports the presence of three informal members in the Kanguk Formation, namely the "Mount Bridgman member", the "bituminous member", and the "Remus Creek ...